Rice-growing environments - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Inland valleys in West Africa: an agro-ecological characterization of rice-growing environments edited by P N Windmeijer and W Andriesse 1993 160pp ISBN 90 70754 320 International Institute for Land Reclamation and Improvement PO Box 45, 6700 Wa